The lantern of lost memories - Hiiragi, Sanaka, 1974- (Grand Central Publishing, 2024)
This is the story of the peculiar and magical photo studio owned by Mr. Hirasaki, a collector of antique cameras. In the dimly lit interior, a paper background is pulled down in front of a wall, and in front of it stands a single, luxurious chair with an armrest on one side. On a stand is a large bellows camera. On the left is the main studio; photos can also be taken in the courtyard. Beyond its straightforward interior, however, is a secret. The studio is, in fact, the door to the afterlife, the place between life and death where those who have departed have a chance--one last time--to see their entire life flash before their eyes via Mr. Hirasaki's "spinning lantern of memories." We meet Hatsue, a ninety-two year old woman who worked as a nursery teacher, the rowdy Waniguchi, a yakuza overseer in his life who is also capable of great compassion, and finally Mitsuru, a young girl who has died tragically young at the hands of abusive parents. Sorting through the many photos of their lives, Mr. Hirasaki also offers guests one guests a second a chance to travel back in time to take a photo of one particular moment in their lives that they wish to cherish in a special way.--